The Influence Of Accounting Conservatism, IOS, And Good Corporate Governance On The Earnings Quality - Yasa, Gerianta Wirawan; Astika, Ida Bagus Putra; Widiariani, Ni Made Ayu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019), 2019)
Study aims to obtain the empirical evidence about the influence of accounting conservatism, investment opportunity set, and good corporate governance on earnings quality of corporates in the Indonesia Stock Exchange. These three factors will certainly affect how earnings are presented to users of financial statements as information in decision making. Secondary data are used in this study. All companies listed in Indonesia Stock Exchange for the period of 2013-2015 are the population in this study. The numbers of samples in this study were 381 companies that were selected by using purposive sampling technique. Multiple linear regression analysis is selected as a data analysis technique. The results show that accounting conservatism has a positive effect on earnings quality. Investment opportunity set has a positive effect on earnings quality. In addition, good corporate governance has no effect on earnings quality. Keywords : Earnings quality, accounting conservatism, investment opportunity set, good corporate governance.